Norwegian general practitioners' knowledge and beliefs about breastfeeding, and their self-rated ability as breastfeeding counsellor - Heidi R Svendby; Beate F Løland; Marianne Omtvedt; Solveig T Holmsen; Per Lagerløv (Taylor & Francis Group, 2016)
Background: Breastfeeding is considered the best infant-feeding method. Norway is one of the leading countries in terms of breastfeeding initiation and duration. To maintain this high breastfeeding rate, it is important to understand the factors that influence breastfeeding. A doctor s advice can improve the rates of breastfeeding initiation and duration, but not all doctors are competent in breastfeeding counselling. Objectives: The aim of this study was to identify the knowledge and beliefs of general practitioners (GPs) about breastfeeding in Norway and to investigate how important they considered guidance about breastfeeding initiation and duration before and after birth. Design: A questionnaire study about knowledge and beliefs according to predefined correct responses and about self-perceived competence as an advisor. Subjects: 122 GPs engaged in apprenticeship for medical students. Results: The response rate was 57%, 69 GPs participated. The questions were answered correctly according to national consensus for 49 % for the knowledge items and 64 % of the belief items. The GPs believed that their guidance was more important after than before birth. Female GPs had more confidence in their guidance ability than male GPs. Confidence in the GPs own guidance after birth was associated with knowledge about contraindications to breastfeeding. Conclusion: Although the GPs expressed beliefs favouring breastfeeding they partly lacked basic knowledge. The GPs confidence in own guidance was better after than before birth and was higher among those with more knowledge. Improved knowledge and emphasis on guidance before birth should be promoted among GPs. Key Points Breastfeeding is the best infant-feeding method. Doctors' advice improves the rates of breastfeeding, but not all doctors have sufficient knowledge. This study mapped the knowledge and beliefs among Norwegian GPs. The study revealed that: GPs partly lacked basic knowledge to effectively promote breastfeeding. GPs had less confidence as advisers during pregnancy than after delivery. Most GPs agreed that knowledge about breastfeeding is basic and should be taught as an integral part of medical school programmes.